Lactose malabsorption in junior high school children - Aswitha D. Budiarso; Deny Sofia; Sri Rezeki S Hadinegoro; Badriul Hegar (Indonesian Pediatric Society Publishing House, 2016)
Background The prevalence of lactose malabsorption varies widely throughout the world. Only people of Caucasian genetic background continue to produce high amount of lactase throughout adulthood. Previous studies in Indonesia revealed that the prevalence of lactose malabsorption was 21-58% in children aged 3-11 years. Objective To determine the prevalence of lactose malabsorption in the older age group and whether a change in milk drinking habit can affect it. Methods A cross sectional descriptive study was conducted on 98 children aged between 12 and 14 years (junior high school) in Jakarta. Lactose malabsorption was evaluated with Lactometer Breath Hydrogen Test (Hoek Loes, Amsterdam). Milk drinking habit was recorded, and drinking at least 1 glass of milk everyday since 6 months or more before the study was considered as regular milk drinking. Results This study showed 73% of the children had lactose malabsorption. Regular milk drinking habit was found in 32 (33%) children and lactose malabsorption occurred in 26. From 66 children who were irregular milk drinkers, lactose malabsorption was found in 46 (70%). Lactose intolerance was about the same in both groups. Conclusion There was an increasing prevalence of lactose malabsorption in older children. Milk drinking habit is a major concern to review the practical implications of lactose malabsorption.